About the article by M.A. Goncharov, Yu.N. Raznitsin, Yu.V. Barkin «SPECIFIC FEATURES OF DEFORMATION OF THE CONTINENTAL AND OCEANIC LITHOSPHERE AS A RESULT OF THE EARTH CORE NORTHERN DRIFT» - Yuri G. Leonov (Геодинамика и тектонофизика, 2015)
The review summary states that studies of the hierarchical subordination of geodynamic systems is top in the scientific agenda, and researches of orientation of the Earth’s surface deformation structures in relation to the elements of the stress field are important. It is noted that the proposed classification of geological objects by ranks is ambiguous, and there is a need for a geodynamic model to provide a basis for studying relationships between the fields of forces, stresses and strains on the surface and processes which take place deep in the core and mantle of the Earth.